CAF-derived miR-642a-3p supports migration, invasion, and EMT of hepatocellular carcinoma cells by targeting SERPINE1 - Zhang, Shuo; Cao, Gang; Shen, Shuijie; Wu, Yu; Tan, Xiying; Jiang, Xiaoyan (PeerJ, 2024)
Background Cancer-associated fibroblasts (CAFs) and hepatocellular carcinoma (HCC) cells interact to promote HCC progression, but the underlying mechanisms remain unclear. Serpin family E member 1 (SERPINE1) has conflicting roles in HCC, and microRNAs (miRNAs) are known to regulate tumor progression through intercellular communication. Therefore, we investigated the potential involvement of miRNA/SERPINE1 axis in crosstalk between CAFs and HCC cells. Methods In this study, candidate miRNAs targeting SERPINE1 3′ UTR were predicted using multiple miRNA databases. The miRNAs and SERPINE1 mRNA expression in Huh7 cells was assessed after co-culture with CAFs using RT-qPCR. Huh7 cell proliferation and invasion were detected after SERPINE1 siRNA. The functions of the CAF-derived miR-642a-3p/SERPINE1 axis in HCC cells were examined using CCK-8, wound healing, transwell assays, western blot, and dual-luciferase reporter assays. Moreover, a orthotopic xenograft model was used to investigate the contribution of miR-642a-3p knockdown in HCC. Results SERPINE1 mRNA expression decreased, while miR-642a-3p expression increased in Huh7 cells co-cultured with CAFs. SERPINE1 knockdown enhanced Huh7 cell proliferation and invasion as well as miR-642a-3p expression. miR-642a-3p overexpression promoted migration, invasion, and epithelial-mesenchymal transition (EMT) in Huh7 cells by targeting SERPINE1, while miR-642a-3p knockdown yielded the opposite effect. Rescue experiments confirmed that SERPINE1 knockdown attenuated the inhibitory effects of miR-642a-3p knockdown on migration, invasion, and EMT in Huh7 cells. Importantly, miR-642a-3p knockdown suppressed growth and EMT in orthotopic liver tumors. Conclusion CAF-derived miR-642a-3p/SERPINE1 axis facilitated migration, invasion, and EMT in the HCC cells, suggesting miR-642a-3p/SERPINE1 axis can be a potential therapeutic target for HCC.
Keywords: Hepatocellular carcinoma; Cancer-associated fibroblasts; miR-642a-3p; SERPINE1; Invasion; EMT